JT-60SA superconducting magnet system. (30th June 2015) - Koide, Y.; Yoshida, K.; Wanner, M.; Barabaschi, P.; Cucchiaro, A.; Davis, S.; Decool, P.; Di Pietro, E.; Disset, G.; Genini, L.; Hajnal, N.; Heller, R.; et al.
Abstract: The most distinctive feature of the superconducting magnet system for JT-60SA is the optimized coil structure in terms of the space utilization as well as the highly accurate coil manufacturing, thus meeting the requirements for the steady-state tokamak research: a conceptually new outer inter-coil structure separated from the casing is introduced to the toroidal field coils to realize their slender shape, allowing large-bore diagnostic ports for detailed plasma measurements. A method to minimize the manufacturing error of the equilibrium-field coils has been established, aiming at the precise plasma shape/position control. A compact butt-joint has been successfully developed for the Central Solenoid, which allows an optimized utilization of the limited space for the Central Solenoid to extend the duration of the plasma pulse.